Identification of Nursing Students' Anxiety and Readiness Facing Ners Competency Tests; Qualitative Study - Suzanna; Inne Yellisni; Gunawan Irianto; Arif Setyo Upoyo (Universitas STRADA Indonesia, 2024)
Background: Having a registration certificate (STR) a nurse must take a competency test as a condition for ownership of the STR. For nursing students, competency tests are a big challenge and complex, so special preparation and attention are needed for students and universities. The implementation of the competency test can create feelings of concern, fear, tension, and anxiety for fear of not passing the competency test. The problem about low graduation rate for ners competency test is influenced by several factors. One of internal factor consist of anxiety and fear facing ners competency test. Purpose: This study identified the perception and experience anxienty dan readiness of few nursing students facing competency test. Method: The study design is qualitative and study was conducted using semi-structured interview. Recruitment of partisipants for the interview was based on purposive sampling methods. Interview were conducted with a maximum 14 participants with saturation data. Analiysis in this study with content analysis. Results: This study explored the perception and experience anxienty dan readiness of few nursing students facing competency test. The current study identified four themes : deep feeling of fear, extreme anxiety, unpreparedness within, surrender and pray. Conclusion: The feelings of anxiety, fear and worry felt by students whether they are taking an exam for the first time or those who are repeating it. In fact, this feeling has quite an impact on the psychological condition, which is also compounded by the student's unpreparedness facing ners competency test.